Inflammation interferes with chemoreception in pigs by altering the neuronal layout of the vomeronasal sensory epithelium - Mechin, Violaine; Asproni, Pietro; Bienboire-Frosini, Cécile; Cozzi, Alessandro; Chabaud, Camille; Arroub, Sana; Mainau, Eva; Nagnan-Le Meillour, Patricia; Pageat, Patrick (Frontiers in Veterinary Science, 2022)
Chemical communication is widely used by animals to exchange information in their environment, through the emission and detection of semiochemicals to maintain social organization and hierarchical rules in groups. The vomeronasal organ (VNO) is one of the main detectors of these messages, and its inflammation has been linked to behavioral changes because it potentially prevents molecule detection and, consequently, the translation of the signal into action. Our previous study highlighted the link between the intensity of vomeronasal sensory epithelium (VNSE) inflammation, probably induced by farm contaminant exposure, and intraspecific aggression in pigs. The aim of this study was to evaluate the cellular and molecular changes that occur during vomeronasalitis in 76 vomeronasal sensorial epithelia from 38 intensive-farmed pigs. Histology was used to evaluate the condition of each VNO and classify inflammation as healthy, weak, moderate, or strong. These data were compared to the thickness of the sensorial epithelium and the number of type 1 vomeronasal receptor cells using anti-Gαi2 protein immunohistochemistry (IHC) and analysis. The presence of odorant-binding proteins (OBPs) in the areas surrounding the VNO was also analyzed by IHC and compared to inflammation intensity since its role as a molecule transporter to sensory neurons has been well-established. Of the 76 samples, 13 (17%) were healthy, 31 (41%) presented with weak inflammation, and 32 (42%) presented with moderate inflammation. No severe inflammation was observed. Epithelial thickness and the number of Gαi2+ cells were inversely correlated with inflammation intensity (Kruskal–Wallis and ANOVA tests, p < 0.0001), while OBP expression in areas around the VNO was increased in inflamed VNO (Kruskal–Wallis test, p = 0.0094), regardless of intensity. This study showed that inflammation was associated with a reduction in the thickness of the sensory epithelium and Gαi2+ cell number, suggesting that this condition can induce different degrees of neuronal loss. This finding could explain how vomeronasalitis may prevent the correct functioning of chemical communication, leading to social conflict with a potential negative impact on welfare, which is one of the most important challenges in pig farming.